2011
DOI: 10.1002/jwmg.314
|View full text |Cite
|
Sign up to set email alerts
|

Management for oak regeneration: Short‐term effects on the bird community and suitability of shelterwood harvests for canopy songbirds

Abstract: Interest in regenerating oaks (Quercus spp.) has promoted use of partial harvesting techniques that create an open forest structure. From 2007 to 2009, we studied songbirds in mixed‐oak forests in southeastern Ohio, comparing shelterwoods recently harvested to 50% stocking and closed‐canopy mature second‐growth. We surveyed birds using distance‐based methods (56 line transects in 18 stands at 4 forests). We intensively investigated suitability of shelterwoods for canopy‐nesting species by examining habitat pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…During the breeding season, we also observed Cerulean Warblers provisioning young at nests in Ohio from 2007 to 2009 (Newell and Rodewald , ). We conducted 30‐min observations of nestling provisioning behavior (51 nests in 39 territories), focusing on the later nestling phase when adults were actively feeding young (>80% of nestlings observed were at least 4 days old based on estimated hatching dates).…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…During the breeding season, we also observed Cerulean Warblers provisioning young at nests in Ohio from 2007 to 2009 (Newell and Rodewald , ). We conducted 30‐min observations of nestling provisioning behavior (51 nests in 39 territories), focusing on the later nestling phase when adults were actively feeding young (>80% of nestlings observed were at least 4 days old based on estimated hatching dates).…”
Section: Methodsmentioning
confidence: 88%
“…We observed foraging behavior from 27 April through 9 July at six sites in two state forests in Vinton and Jackson counties. Three sites had recently been partially harvested to ∼50% stocking (Newell and Rodewald , ). During the non‐breeding season, we studied Cerulean Warblers at six shade coffee farms on the western slopes of the Cordillera de Merida in the Venezuelan Andes (Bakermans et al , , Newell et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies in hardwood forests also have found that densities of many species are not detectably changed following low-intensity prescribed burns (Aquilani et al, 2000;Artman et al, 2001) or other silvicultural treatments with a moderate to high level of canopy retention (Moorman and Guynn, 2001;Newell and Rodewald, 2012).…”
Section: Breeding Birdsmentioning
confidence: 93%
“…Removing the residual canopy in stages, as is sometimes done, perhaps may extend the benefits for canopy-dependent birds. However, the benefits for these species will eventually end due to often complete overstory removal later in the cutting cycle (Newell and Rodewald, 2012). Further, as these stands age the understory will eventually become unsuitable for some gap-dependent species.…”
Section: Medium Rba Forest Bird Managementmentioning
confidence: 99%
“…Management strategies specifically intended to benefit Cerulean Warblers may be implemented across large areas in their core breeding range, and thus may have a large effect on the overall bird community. While studies within the core range of Cerulean Warblers have examined effects of specific timber harvest prescriptions on bird communities (e.g., Newell and Rodewald, 2012), knowledge of the effects of Cerulean Warbler management on a full range of early to late successional forest bird species is lacking.…”
Section: Introductionmentioning
confidence: 99%